Exploring the Role of Perceived Value and Customer Attitude in Co-Branding: Impact on Purchase Intention for Somethinc Cosmetics X Bittersweet by Najla - Nurrosidah, Ali; Djatmika, Ery Tri; Dewi, Titis Shinta (Journal of Applied Business, Taxation and Economics Research, 2025)
This study explores the effect of co-branding on the purchase intention of collaboration products between Somethinc and Bittersweet by Najla, focusing on perceived value and customer attitude. Using a quantitative approach with data analyzed via PLS-SEM through the SmartPLS 3.2.9 application, the research involved 385 respondents who use Somethinc products. The study supports seven hypotheses regarding investigates how co-branding influences the intention to purchase. Findings indicate that the compatibility of products and brands in co-branding significantly influences consumer purchase intention. Co-branding also positively affects perceived value, with better co-branding leading to higher perceived value among consumers. Additionally, co-branding impacts customer attitude, and both perceived value and customer attitude significantly affect purchase intention for collaboration products. Notably, the direct effect of co-branding on intention to purchase is smaller than the indirect effect through perceived value and customer attitude. This highlights that perceived value and customer attitude are strong intervening variables that moderate the effect of co-branding on intention to purchase. This research provides an understanding that co-branding for different product categories must have compatibility in products, brands, and promotions to target the same segment, so as to increase consumer perceived value and consumer attitudes towards collaboration products, thus influencing consumers to be interested in buying collaboration products.